A Comprehensive Study of Recent Advances in Time-Domain Astronomy: Stellar Encounters, Tidal Disruption Events, and Multi-Messenger Observations: Studi Komprehensif tentang Kemajuan Terkini dalam Astronomi Domain Waktu: Pertemuan Bintang, Peristiwa Gangguan Pasang Surut, dan Pengamatan Multi-Messenger - Imad Kamil Zayer (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Time-domain astronomy has advanced significantly with the development of high-cadence surveys and multi-messenger observational techniques that enable the study of dynamic astrophysical phenomena. Specific Background: Modern facilities such as Gaia DR3, the Zwicky Transient Facility, and H.E.S.S. provide extensive datasets for analyzing stellar encounters, tidal disruption events, and high-energy gamma-ray emissions. Knowledge Gap: Despite the availability of these datasets, integrated analysis across these domains remains limited, particularly in connecting stellar dynamics, accretion processes, and particle acceleration within a unified framework. Aims: This study aims to examine recent developments in stellar encounters, repeating partial tidal disruption events, and gamma-ray emissions using multi-messenger observations. Results: The findings show that approximately 2% of Sun-like stars experience close encounters within 100 AU over 4.6 Gyr, with Gliese 710 predicted to approach within 0.051 pc. The event AT 2020vdq demonstrates repeating partial tidal disruption with a 947-day interval and consistent spectral properties, while Eta Carinae exhibits very-high-energy gamma-ray emission with a spectral index of 3.3. Novelty: The study integrates multiple astrophysical domains into a cohesive analysis supported by observational data. Implications: The results support the use of combined astrometric, optical, and high-energy observations for studying extreme astrophysical processes and future multi-messenger research. Keywords: Time-Domain Astronomy, Stellar Encounters, Tidal Disruption Events, Gamma-Ray Emission, Multi-Messenger Observations Key Findings Highlights Close stellar passages show measurable long-term effects on planetary system dynamics Recurrent flaring behavior confirms partial disruption scenarios in galactic nuclei High-energy signals reveal particle acceleration in colliding-wind binary systems